Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To solve the system of equations:
[tex]\[ \begin{cases} 2x = 5y + 4 \\ 3x - 2y = -16 \end{cases} \][/tex]
we can use the method of substitution or elimination. Let's go step by step using substitution in this case.
1. Equation 1: [tex]\(2x = 5y + 4\)[/tex]
Solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{5y + 4}{2} \][/tex]
2. Substitute [tex]\(x\)[/tex] in Equation 2:
[tex]\[ 3 \left( \frac{5y + 4}{2} \right) - 2y = -16 \][/tex]
3. Multiply both sides by 2 to clear the fraction:
[tex]\[ 3(5y + 4) - 4y = -32 \][/tex]
4. Distribute and simplify:
[tex]\[ 15y + 12 - 4y = -32 \][/tex]
[tex]\[ 11y + 12 = -32 \][/tex]
5. Isolate [tex]\(y\)[/tex]:
[tex]\[ 11y = -32 - 12 \][/tex]
[tex]\[ 11y = -44 \][/tex]
[tex]\[ y = \frac{-44}{11} \][/tex]
[tex]\[ y = -4 \][/tex]
6. Substitute [tex]\(y\)[/tex] back into Equation 1 to find [tex]\(x\)[/tex]:
[tex]\[ 2x = 5(-4) + 4 \][/tex]
[tex]\[ 2x = -20 + 4 \][/tex]
[tex]\[ 2x = -16 \][/tex]
[tex]\[ x = \frac{-16}{2} \][/tex]
[tex]\[ x = -8 \][/tex]
Therefore, the solution to the system of equations is [tex]\((-8, -4)\)[/tex].
To determine which option matches our solution:
- [tex]\((-8, -4)\)[/tex]: Yes, this matches our solution.
Thus, the correct answer is [tex]\((-8, -4)\)[/tex], which corresponds to the option 1.
[tex]\[ \begin{cases} 2x = 5y + 4 \\ 3x - 2y = -16 \end{cases} \][/tex]
we can use the method of substitution or elimination. Let's go step by step using substitution in this case.
1. Equation 1: [tex]\(2x = 5y + 4\)[/tex]
Solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{5y + 4}{2} \][/tex]
2. Substitute [tex]\(x\)[/tex] in Equation 2:
[tex]\[ 3 \left( \frac{5y + 4}{2} \right) - 2y = -16 \][/tex]
3. Multiply both sides by 2 to clear the fraction:
[tex]\[ 3(5y + 4) - 4y = -32 \][/tex]
4. Distribute and simplify:
[tex]\[ 15y + 12 - 4y = -32 \][/tex]
[tex]\[ 11y + 12 = -32 \][/tex]
5. Isolate [tex]\(y\)[/tex]:
[tex]\[ 11y = -32 - 12 \][/tex]
[tex]\[ 11y = -44 \][/tex]
[tex]\[ y = \frac{-44}{11} \][/tex]
[tex]\[ y = -4 \][/tex]
6. Substitute [tex]\(y\)[/tex] back into Equation 1 to find [tex]\(x\)[/tex]:
[tex]\[ 2x = 5(-4) + 4 \][/tex]
[tex]\[ 2x = -20 + 4 \][/tex]
[tex]\[ 2x = -16 \][/tex]
[tex]\[ x = \frac{-16}{2} \][/tex]
[tex]\[ x = -8 \][/tex]
Therefore, the solution to the system of equations is [tex]\((-8, -4)\)[/tex].
To determine which option matches our solution:
- [tex]\((-8, -4)\)[/tex]: Yes, this matches our solution.
Thus, the correct answer is [tex]\((-8, -4)\)[/tex], which corresponds to the option 1.
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.